Coping Health Information Fatigue in the Digital Era: Tabayyun Analysis Perspective - Indri Rachmawati; Tri Nur Aini Noviar; Raditya Pratama Putra; Yulianti (UPT Publikasi Ilmiah UNISBA, 2024)
The Indonesian Government imposed social distancing to contain the spread of novel coronavirus disease 2019. Enforcement of these regulations makes social media prevalent for seeking medical information after pandemic. Experiencing overload information can make individuals feel fatigued while processing the information they receive, including health information amidst the COVID-19 pandemic. Tabayyun is an attempt to find out unclear information by checking information. This means that tabayyun process involves checking and selecting information carefully. This article is a descriptive research report that tries to describe the attitude of tabayyun to Muslim families in receiving health information, especially in the digital era. Specifically, this research aims to give details of The tabayyun attitude that must be developed in the digital era and The behavior of Muslim families when doing tabayyun via social media. How individuals behave when receiving information needs to be developed to anticipate the overload caused by the rapid flow of health information. The findings showed that attitude of tabayyun was crucial in receiving various health information. The habit of constantly checking the health information received needs to be trained and applied